Efficiency of the program of correction of emotional-volitional sphere of swimmers with violations of intellect on a test 4х50 m. - Babich Nataliia Leonidovna (Kharkov National Pedagogical University, 2011)
The comparative analysis of results of implementation of test is resulted 4х50 m by swimmers with violations of mental development before and after introduction of the experimental program of correction emotionally of volitional sphere of such sportsmen. Grounded expedience of the use of test 4х50 m as one of criteria of estimation of ability of swimmers to mobilization and display of conations on a background a fatigue. It is well-proven that the experimental program positively influenced on the dynamics of stabilizing of results of swimming of the 4 test cuttings-off in the conditions of hard rest on a background a fatigue.